2021
DOI: 10.1155/2021/5566234
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Maternal Serum Screens in the Second Trimester as Markers of Placentally Mediated Complications Later in Pregnancy: A Systematic Review and Meta-Analysis

Abstract: Background. Multiple-marker, maternal serum screening (MSS) has been the cornerstone of prenatal diagnosis since the 1980s. While combinations of these markers are used to predict fetal risk of Down syndrome and other genetic conditions, there is some evidence that individual markers may also predict nongenetic pregnancy complications, particularly those related to placental dysfunction. The objective of this meta-analysis was to investigate the utility of false-positive, second-trimester MSS for Down syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…However, there was no significant association between these variables and growth restriction and preterm birth. [ 2 ] Yazdani et al . [ 13 ] conducted a cohort study on 300 pregnant women and found a higher rate of preeclampsia ( p = 0.008), SGA ( p = 0.028), and premature rupture of membrane ( p = 0.004) among those who had positive quad test results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no significant association between these variables and growth restriction and preterm birth. [ 2 ] Yazdani et al . [ 13 ] conducted a cohort study on 300 pregnant women and found a higher rate of preeclampsia ( p = 0.008), SGA ( p = 0.028), and premature rupture of membrane ( p = 0.004) among those who had positive quad test results.…”
Section: Discussionmentioning
confidence: 99%
“…All women should be screened before the twentieth gestational week, regardless of maternal age. [ 1 2 ]…”
Section: Introductionmentioning
confidence: 99%